CASE REPORT : OSTEOARTHRITIS - Putu Imayati; Gede Kambayana (E-Jurnal Medika Udayana, 2014)
Osteoarthritis is a degenerative joint disease in which the affected joint is usually the largejoint and unilateral. Prevalence of osteoarthritis in Indonesia, 15.5% in men and 12.7% inwomen, where the incidence is increasing with age. Osteoarthritis is more common anidiopathic disease or unknown cause although there is also a secondary cause such astrauma, infection, neurological or metabolic disorders. The usual complaints  that perceivedby osteoarthritis patients is pain in the affected joint, especially after the load on the joint.Therapy in osteoarthritis is usually symptomatic, which include the control of risk factors,physiotherapy and pharmacological.